High-rate high-nickel cobalt-free positive electrode material as well as preparation method and application thereof
By using MBene-type material cladding on high nickel cobalt-free positive electrode material, the problem of poor binding force between the cladding and the substrate is solved, the rate performance and cycle stability of lithium-ion batteries are improved, and the conductivity is achieved and more stable battery performance.
Patent Information
- Application Number
- CN202411708642.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The poor bonding force of the cladding layer of the high-nickel cobalt-free cathode material and the cathode material matrix leads to insufficient conductivity and chemical stability, affecting the rate performance and cycle stability of lithium-ion batteries.
MBene-type materials are used as the cladding layer. After grinding the positive electrode material matrix, MBene-type materials are coated using solid phase reaction method or spray drying method to form a porous structure and a high conductive cladding layer to improve the positive electrode material. chemical stability and conductivity.
It significantly improves the rate performance and cycle stability of lithium-ion batteries, reduces changes in pulping viscosity, and extends the cycle life of the battery.
Smart Images

Figure CN119208592A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high-nickel and cobalt-free positive electrode materials for lithium-ion batteries, and in particular relates to a high-rate high-nickel and cobalt-free positive electrode material and a preparation method and application thereof. Background Art
[0002] With people's extreme pursuit of high energy density and low cost, the nickel content of lithium-ion battery positive electrode materials is getting higher and higher, and the cobalt content is getting lower and lower or even cobalt-free. The two factors of increased nickel content and absence of cobalt lead to increased residual lithium in positive electrode materials, serious lithium-nickel mixing, poor thermal stability, easy breakage of particles, and poor rate performance and cycle stability. For ultra-high nickel and cobalt-free materials with Ni>90%, these problems are more prominent.
[0003] The traditional coating operation is generally to directly mix the coating with the cathode material matrix by dry or wet method, and then obtain the coated modified cathode material by low temperature annealing. Because the surface of the cathode material matrix is uneven, the coating layer has a weak bonding force with the cathode material matrix, and fails to completely cover the entire particle surface, resulting in poor stability of the later electrical performance. Traditional coatings are generally metal oxides, which are difficult to fully react with the residual lithium on the surface of the cathode material matrix. Because the residual lithium on the surface is relatively dense in the pits or gaps of the particles, it is difficult for the coating to fully contact it, resulting in a considerable portion of it still existing in the initial oxide state, which in turn leads to poor conductivity on the surface of the cathode material, which is not conducive to the later electrical performance.
[0004] Patent document CN118248856A discloses a method for preparing a positive electrode material for an aqueous zinc ion battery based on a composite of a single-layer MoB MBene and 1T-MoS2. The specific process is: MoB MBene is subjected to ultrasonic treatment to obtain a single-layer MoB MBene, and then it is mixed with MoO3, urea and thioacetamide and placed in an autoclave to react at 200°C for 12 hours, and then washed with anhydrous ethanol and distilled water, and freeze-dried. In order to further improve the performance, aniline, hydrochloric acid and ammonium persulfate are added to the material at low temperature and reacted for 12 hours. A layer of polyaniline can be coated on the material, which serves to enhance the stability of the material structure. This patent uses a single-layer MoB MBene as a skeleton and grows 1T-MoS2 in situ outside, so that the prepared electrode material has excellent electronic conductivity and good structural stability. The coated polyaniline further ensures the cyclic stability of the material during charge and discharge. However, the patent prepares aqueous zinc-ion battery positive electrode materials and the single-layer MoB MBene is used as a skeleton in the preparation process of aqueous zinc-ion battery positive electrode materials to achieve in-situ growth of 1T-MoS2 and coating of a polyaniline coating layer. Patent document CN118522875A discloses a modified positive electrode material and its preparation method and application, wherein the modified positive electrode material includes a positive electrode material matrix and a coating layer arranged on the surface of the positive electrode material matrix, and the coating layer includes a fluorine-containing polymer and a metal oxide coated MBene nanomaterial. The modified positive electrode material has excellent charge and discharge performance and cycle performance at a high cut-off voltage. The coating layer prepared in the coating modification process of this patent includes fluoropolymer and metal oxide coated MBene nanomaterials, not a single MBene nanomaterial, and in the coating modification process, the fluoropolymer and metal oxide coated MBene nanomaterials are added to the second organic solvent for dispersion, and then the second organic solvent dispersion of the positive electrode material matrix is added, stirred, evaporated and dried to obtain a powder; the powder is subjected to a fusion reaction to obtain a modified positive electrode material. The coating modification step adopts a direct wet mixing method, which to a certain extent cannot effectively achieve the dense and uniform coating of the fluoropolymer and metal oxide coated MBene nanomaterials on the surface of the positive electrode material matrix, and it cannot effectively ensure the stable coating of the fluoropolymer and metal oxide coated MBene nanomaterials on the surface of the positive electrode material matrix, thereby effectively preventing the coating layer from peeling off and falling off. Summary of the invention
[0005] The present invention aims to solve the problems in the prior art that the coating layer of a high-nickel cobalt-free positive electrode material has poor bonding strength with the positive electrode material matrix, the coating layer material has poor conductivity and chemical stability, which in turn leads to poor surface stability of the modified positive electrode material, large viscosity changes when used in slurrying for lithium-ion batteries, and the prepared lithium-ion batteries have poor rate performance and poor cycle stability. A high-rate high-nickel cobalt-free positive electrode material and a preparation method thereof are provided. The high-nickel cobalt-free positive electrode material prepared by the method has a porous structure inside, and a MBene-type material coating layer with stable chemical properties and high electrical conductivity on the surface. When the high-nickel cobalt-free positive electrode material is used in a lithium-ion battery, the slurrying viscosity changes little, the prepared lithium-ion battery has good rate performance and significantly improved cycle stability.
[0006] The present invention adopts the following technical solution to solve the above technical problems: a high-rate high-nickel cobalt-free positive electrode material, whose chemical formula is LiNi x Mn 1-x-y-z M y N z O2, M is one or more of Al, Zr, Y, W, Nb, Ce, Ti, Mg, Sr, B, P or Si, N is a MBene material coating layer, and the MBene material is MoB, Mo 1.33 One or more of B, Zr2B2, MnB, Cr2B2, Fe2B2 or TiB, 0.5 <x<1,0<y<0.1,0<z<0.1,0<x+y+z<1。
[0007] MBene-type materials are two-dimensional transition metal borides with diversity and controllability. Their structure and properties can be adjusted by changing the M element, incorporating the M' element, and forming different surface functional groups. This type of material has good mechanical strength and hardness, as well as certain chemical stability, acid and alkali corrosion resistance, and oxidation resistance. It also has good lithium ion diffusion and charge transfer capabilities, and can achieve high capacity, high stability, and high rate performance. For lithium-ion battery cathode materials, it is an excellent coating material.
[0008] The invention provides a method for preparing a high-rate, high-nickel, cobalt-free positive electrode material, and the specific process is: a porous precursor is selected for lithium sintering to obtain a positive electrode material matrix, and then the positive electrode material matrix is polished with a polishing agent, and after the polishing is completed, the polishing agent and the fine powder produced by the polishing are separated, and finally, MBene-type materials are coated, and then annealing and sintering are performed to obtain a high-rate, high-nickel, cobalt-free positive electrode material having a porous structure inside and a coating layer with stable chemical properties and high electrical conductivity on the surface; the polishing agent is a powder or dispersion of one or more of cerium oxide, silicon oxide, zirconium oxide, aluminum oxide, iron oxide, chromium oxide or stearic acid; preferably one or more of cerium oxide, silicon oxide, zirconium oxide or aluminum oxide, because the metal elements in cerium oxide, silicon oxide, zirconium oxide and aluminum oxide are relatively harmless to the positive electrode material matrix, and even if a small part of them remains on the surface of the positive electrode material matrix, it will not have an adverse effect on the performance of the electrical properties of the positive electrode material in the later stage.
[0009] It is further defined that the D50 of the polishing agent particles is 10nm~50μm; if the particle size of the polishing agent particles is too large, it will have a greater destructive force on the positive electrode material matrix during the polishing process, easily causing particle cracks or even breakage, resulting in poor electrical performance in the later stage; if the particle size of the polishing agent particles is too small, the polishing force is weak and the polishing efficiency is low.
[0010] It is further specified that the amount of polishing agent used accounts for 1% to 20% of the weight of the positive electrode material matrix; if the amount of polishing agent used is too much, the cost of the polishing agent raw material and the separation from the positive electrode material matrix will increase; if the amount of polishing agent used is too little, the polishing time will be extended and the polishing efficiency will be low.
[0011] It is further defined that the method for polishing the positive electrode material matrix is selected from one or more of high-speed mixing polishing, grinding polishing, ball milling polishing or fusion machine polishing.
[0012] It is further defined that the method for separating the polished positive electrode material matrix from the polishing agent and the fine powder produced by polishing is selected from one or more of cyclone separation, ultrasonic screening separation, centrifugal separation, membrane separation, sedimentation separation or magnetic separation; preferably one or more of cyclone separation or ultrasonic screening separation.
[0013] It is further specified that after the polished positive electrode material matrix is separated from the polishing agent and the fine powder produced by polishing, the residual proportion of the polishing agent is within 5% of the weight of the added polishing agent; if the residual proportion of the polishing agent is too much, it will lead to an increase in inactive ingredients in the final positive electrode material and a decrease in battery capacity.
[0014] It is further specified that the sphericity of the particles of the positive electrode material matrix after grinding is 85%~100%; if the sphericity of the particles of the positive electrode material matrix is too low, the sphericity is relatively poor, indicating that the grinding effect is not good. During the subsequent MBene material coating, the coating effect at sharp corners or gaps is poor, and it is difficult to form a dense and uniform coating layer, which is not conducive to the subsequent electrical performance.
[0015] It is further defined that the coating method of MBene-type materials is selected from one or more of solid phase reaction method, spray drying method, hydrothermal or solvothermal method, sol-gel method, microemulsion coating method, heterogeneous nucleation method, supercritical fluid method, chemical vapor deposition method or microencapsulation method; preferably one or more of solid phase reaction method or spray drying method.
[0016] The present invention also provides a lithium ion battery, wherein the positive electrode of the lithium ion battery is prepared from the high-rate high-nickel cobalt-free positive electrode material.
[0017] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The present invention uses MBene materials as the coating layer. On the one hand, the surface chemical properties of the high-nickel cobalt-free positive electrode material are stable, the slurry stability is higher during the slurrying of the lithium-ion battery, the viscosity changes less, and the side reaction with the electrolyte is reduced during the cycle, thereby achieving better cycle stability of the lithium-ion battery; on the other hand, the MBene material has high ionic conductivity, and the lithium-ion battery prepared from the high-nickel cobalt-free positive electrode material coated with the MBene material has better rate performance.
[0018] 2. The present invention first grinds the positive electrode material matrix before coating. On the one hand, the sphericity of the positive electrode material matrix particles can be higher, the fluidity can be better, and there are fewer sharp-angled pits or protruding particles on the surface, which makes it easier to achieve dense and uniform coating on the surface of the positive electrode material matrix particles; on the other hand, it is beneficial for the coating layer to be more tightly and firmly combined with the positive electrode material matrix, so that the coating layer is not easy to peel off or fall off during the charging and discharging process of the high-nickel cobalt-free positive electrode material, and the long-term electrical performance is more stable and the cycle life is longer. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The slurry viscosity change curves of the positive electrode materials in Examples 1-3 and Comparative Examples 1-2 are shown in FIG.
[0020] Figure 2 Full-electric rate performance curves for the positive electrode materials in Examples 1-3 and Comparative Examples 1-2.
[0021] Figure 3 Fully electric cycle performance curves were prepared for the positive electrode materials in Examples 1-3 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0022] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention. Example 1
[0023] Choose Ni 0.92 Mn 0.075 B 0.005 The (OH)2 porous precursor was sintered with lithium hydroxide at a ratio of 1:1.05 at 760°C to obtain the positive electrode material matrix LiNi 0.92 Mn 0.075 B 0.005 O2; then grind the positive electrode material matrix with cerium oxide powder with a D50 of 1 μm, which accounts for 10% of the weight of the positive electrode material matrix. The specific operation process is to add the positive electrode material matrix and cerium oxide into the grinder, start automatic grinding until the sphericity of the positive electrode material matrix reaches 94%, and then cyclone separation to remove cerium oxide and the ground fine powder until the residual weight ratio of cerium oxide is less than 5%; Mo 1.33 The B dispersion was coated onto the polished surface of the positive electrode material substrate by spray drying, and then annealed at 600°C for 6 hours to obtain LiNi 0.91 Mn 0.075 B 0.005 (Mo 1.33 B) 0.01 O2 positive electrode material. Example 2
[0024] Choose Ni 0.94 Mn 0.04 W 0.02 The (OH)2 porous precursor was sintered with lithium hydroxide at a ratio of 1:1.05 at 740°C to obtain the positive electrode material matrix LiNi 0.94 Mn 0.04 W 0.02 O2; then the positive electrode material matrix is polished with silicon oxide powder with a D50 of 5 μm, which accounts for 5% of the weight of the positive electrode material matrix. The specific operation process is to add the positive electrode material matrix and silicon oxide into the fusion machine, adjust the rotor speed to adjust the pressure of the polishing agent powder sprayed in the fixed pressure head until the sphericity of the positive electrode material matrix reaches 92%, and then pass through an ultrasonic vibration screen to separate and remove silicon oxide and the ground fine powder until the residual weight ratio of silicon oxide is less than 5%; Fe2B2 dispersion and the polished positive electrode material matrix are added to a high-pressure reactor lined with polytetrafluoroethylene, and dispersant ethylene glycol is added at the same time, and the reaction is carried out at 120°C for 12 hours. After the obtained product is separated from the solid and liquid and washed, it is placed in a vacuum oven and dried at 80°C for 10 hours, and then annealed at 600°C for 6 hours to obtain LiNi 0.93 Mn 0.04 W0.02 (Fe2B2) 0.01 O2 positive electrode material. Example 3
[0025] Choose Ni 0.96 Mn 0.03 Al 0.01 The (OH)2 porous precursor was sintered with lithium hydroxide at a ratio of 1:1.05 at 720°C to obtain the positive electrode material matrix LiNi 0.96 Mn 0.03 Al 0.01 O2; then the positive electrode material matrix is polished with a zirconium oxide dispersion with a solid content of 15wt% and a D50 of 500nm. The zirconium oxide particles in the zirconium oxide dispersion account for 15% of the weight of the positive electrode material matrix. The specific operation process is to add the positive electrode material matrix and zirconium oxide into a ball mill, and add polyurethane balls and anhydrous ethanol at the same time, and perform wet polishing until the sphericity of the positive electrode material matrix reaches 90%. After the polishing, the polyurethane balls are first taken out and then centrifuged. The pore size of the filter cloth is 2μm to remove the zirconium oxide and the fine powder from the grinding powder. The filter cake is vacuum dried until the residual weight ratio of zirconium oxide is less than 5%, and the polished positive electrode material matrix powder is obtained; the TiB powder and the polished positive electrode material matrix powder are fully mixed by a high-speed mixing method, and then annealed at 650℃ for 6 hours to obtain LiNi 0.93 Mn 0.03 Al 0.01 (TiB) 0.03 O2 positive electrode material.
[0026] Comparative Example 1 The steps are basically the same as those in Example 1, except that: 1.33 B. The positive electrode material substrate is polished before coating.
[0027] Comparative Example 2 The steps are basically the same as those in Example 1, except that the polished positive electrode material substrate is not coated with Mo. 1.33 B material.
[0028] Particle sphericity (roundness) test By combining electron microscopy with image processing technology, image processing software is used to binarize the electron microscopy image of the sample, and the resulting image is regarded as a two-dimensional projection of a particle group. The number of pixels that make up each particle projection is statistically calculated and then converted into the pixel area, pixel perimeter, etc. of each particle. Based on this information, the software can accurately calculate the sphericity (roundness) description parameters of any particle in the image.
[0029] Electrical performance test 1. Electrical performance test: The battery involved is a 604062 soft-pack battery, and the specific production steps are as follows: Step 1): The main material: SP: CNT: PVDF is mixed in a weight ratio of 95.5%: 1.0%: 1.7%: 1.8%, and the mixture is stirred and dispersed at high speed in a dual planetary power mixer to obtain a full-electric slurry; Step 2): The full-electric slurry is coated, baked, rolled, cut, wound, injected, and sealed to obtain a 604062 type soft-pack battery.
[0030] 2. Viscosity change test: Take 150 mL of the all-electric slurry obtained in step 1), place it in an open environment with a relative humidity of ≤60%, test the viscosity every hour, and place it for a total of 17 hours.
[0031] 3. Rate performance test: The 604062 type soft-pack battery obtained in step 2) was charged at 1C at room temperature 23±2°C and in the voltage range of 2.75-4.2V, and discharged at 1C, 2C, 3C, 4C, and 5C, and the discharge capacity ratios of 1C / 1C, 2C / 1C, 3C / 1C, 4C / 1C, and 5C / 1C were calculated respectively.
[0032] 4. Cycle performance test: The 604062 soft-pack battery obtained in step 2) was subjected to a 1C charge and discharge cycle test at room temperature 23±2°C and within a voltage range of 2.75-4.2V until the capacity decayed to 80% of the first-week capacity.
[0033] The positive electrode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were used to prepare full-electrode materials and the slurry viscosity test, rate performance test and cycle stability performance test were performed. Figures 1 to 3 .
[0034] from Figure 1 It can be seen that the slurry viscosity of the positive electrode material prepared in Examples 1 to 3 is significantly lower, and the fluctuation range is relatively small, indicating that the slurry state is more stable with the extension of the storage time; the slurry viscosity of the positive electrode material prepared in Comparative Example 1 is close to that of Examples 1 to 3 at the initial stage of placement, and the slurry viscosity begins to fluctuate greatly with the extension of time, indicating that the slurry stability gradually deteriorates. This is because the positive electrode material matrix is not polished before coating, resulting in weak bonding between the coating layer and the positive electrode material matrix. In the ultrasonic vibration screen screening process of the finished positive electrode material and the high-speed stirring process of the slurry for soft-pack battery production, there is a great possibility that the coating layer will partially peel off or fall off, resulting in exposure of the internal surface of the positive electrode material with relatively high residual alkali, which in turn causes the slurry to fluctuate greatly with the extension of the storage time.
[0035] from Figure 2It can be seen that the rate performance of the positive electrode materials in Examples 1 to 3 is significantly better than that in Comparative Examples 1 to 2, indicating that the rate performance of the positive electrode materials for preparing the full-electric can be effectively improved by sintering the porous structure precursor, first polishing the positive electrode material substrate, and then coating the highly conductive MBene material as a coating layer.
[0036] from Figure 3 It can be seen that the cycle life and cycle stability of the positive electrode materials in Examples 1 to 3 are significantly better than those in Comparative Examples 1 to 2, indicating that the coating layer on the surface of the positive electrode material fully plays a role in isolating electrolyte corrosion and inhibiting side reactions, thereby making the cycle stability of the prepared full-electric better; the coating layer on the surface of the positive electrode material plays a role in improving the ionic conductivity, thereby making the rate performance of the prepared full-electric better.
[0037] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.
Claims
1. A high-rate, high-nickel, cobalt-free cathode material, characterized in that: The chemical formula of this high-rate, high-nickel, cobalt-free cathode material is LiNi x Mn 1-x-y-z M y N z O2, M is one or more of Al, Zr, Y, W, Nb, Ce, Ti, Mg, Sr, B, P or Si, N is a MBene material coating layer, and the MBene material is MoB, Mo 1.33 One or more of B, Zr2B2, MnB, Cr2B2, Fe2B2 or TiB, 0.5 <x<1,0<y<0.1,0<z<0.1,0<x+y+z<1。 2. A method for preparing the high-rate high-nickel cobalt-free positive electrode material according to claim 1, characterized in that The specific process is: a porous precursor is selected for lithium sintering to obtain a positive electrode material matrix, and then the positive electrode material matrix is polished with a polishing agent. After the polishing treatment is completed, the polishing agent and the fine powder produced by the polishing are separated, and finally coated with an MBene material, and then annealed and sintered to obtain a high-rate high-nickel cobalt-free positive electrode material with a porous structure inside and a coating layer with stable chemical properties and high electrical conductivity on the surface; the polishing agent is a powder or dispersion of one or more of cerium oxide, silicon oxide, zirconium oxide, aluminum oxide, iron oxide, chromium oxide or stearic acid.
3. The method for preparing a high-rate high-nickel cobalt-free positive electrode material according to claim 2, characterized in that: The D50 of the abrasive particles is 10nm~50μm.
4. The method for preparing a high-rate high-nickel cobalt-free positive electrode material according to claim 2, characterized in that: The amount of the polishing agent used accounts for 1% to 20% of the weight of the positive electrode material matrix.
5. The method for preparing a high-rate high-nickel cobalt-free positive electrode material according to claim 2, characterized in that: The method for polishing the positive electrode material matrix is selected from one or more of high-speed mixing polishing, grinding polishing, ball milling polishing or fusion machine polishing.
6. The method for preparing a high-rate high-nickel cobalt-free positive electrode material according to claim 2, characterized in that: The method for separating the polished positive electrode material matrix from the polishing agent and the fine powder produced by polishing is selected from one or more of cyclone separation, ultrasonic screening separation, centrifugal separation, membrane separation, sedimentation separation or magnetic separation.
7. The method for preparing a high-rate high-nickel cobalt-free positive electrode material according to claim 2, characterized in that: After the polished positive electrode material matrix is separated from the polishing agent and the fine powder produced by the polishing, the residual proportion of the polishing agent is within 5% of the weight of the added polishing agent.
8. The method for preparing a high-rate, high-nickel, cobalt-free positive electrode material according to claim 2, characterized in that: The particle sphericity of the polished positive electrode material matrix is 85%~100%.
9. The method for preparing a high-rate high-nickel cobalt-free positive electrode material according to claim 2, characterized in that: The coating method of MBene-type materials is selected from one or more of solid phase reaction method, spray drying method, hydrothermal or solvothermal method, sol-gel method, microemulsion coating method, heterogeneous nucleation method, supercritical fluid method, chemical vapor deposition method or microencapsulation method.
10. A lithium ion battery, characterized in that: The positive electrode of the lithium-ion battery is prepared from the high-rate, high-nickel, cobalt-free positive electrode material described in claim 1.
Citation Information
Patent Citations
Cobalt-free high-nickel positive electrode material and preparation method thereof, lithium ion battery positive electrode and lithium ion battery
CN113023794A
Novel two-dimensional transition metal boride, preparation method thereof and application of novel two-dimensional transition metal boride as energy storage electrode material
CN114956108A
Coated modified high-nickel ternary positive electrode material as well as preparation method and application thereof
CN115425214A
Positive electrode material and preparation method and application thereof
CN115714174A
Positive electrode active material and preparation method and application thereof
CN116504939A
